Theory and Applications of Models of Computation 10th International Conference, TAMC 2013, Hong Kong, China, May 20-22, 2013. Proceedings - Chan, T-H. Hubert; Lau, Lap Chi.; Trevisan, Luca.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 10th International Conference on Theory and Applications of Models of Computation, TAMC 2013, held in Hong Kong, China, in May 2013. The 31 revised full papers presented were carefully reviewed and selected from 70 submissions. Bringing together a wide range of researchers with interests in computational theory and applications, the papers address the three main themes of the conference which were computability, complexity, and algorithms and present current research in these fields with aspects to theoretical computer science, algorithmic mathematics, and applications to the physical sciences.
Computability -- complexity -- algorithms -- present current research.
Keywords: Computer science; Data structures (Computer science).; Information theory; Computer software; Logic design; Computer Science; Theory of Computation; Mathematics of Computing; Algorithm Analysis and Problem Complexity; Logics and Meanings of Programs; Data Structures, Cryptology and Information Theory; Mathematical Logic and Formal Languages